"Blockbotting Dissent": Publics, Counterpublics, and Algorithmic Public Sphere(s) - Gosse, Chandell Enid; O’Meara, Victoria Jane (Stream: Interdisciplinary Journal of Communication, 2018)
In 2014, at the height of gamergate hostilities, a blockbot was developed and circulated within the gaming community that allowed subscribers to automatically block upwards of 8,000 Twitter accounts. "Ggautoblocker" as it was called, was designed to insulate subscribers’ Twitter feeds from hurtful, sexist, and in some cases deeply disturbing comments. In doing so it cast a wide net and became a source of considerable criticism from many in the industry and games community. During this time, the International Game Developers Association (IGDA) 2015 Video Game Developer Satisfaction Survey was circulating, resulting in a host of comments on the blockbot from workers in the industry. In this paper we analyze these responses, which constitute some of the first empirical data on a public response to the use of autoblocking technology, to consider the broader implications of the algorithmic structuring of the online public sphere. First, we emphasize the important role that ggautoblocker, and similar autoblocking tools, play in creating space for marginalized voices online. Then, we turn to our findings, and argue that the overwhelmingly negative response to ggautoblocker reflects underlying anxieties about fragmenting control over the structure of the online public sphere and online public life. In our discussion, we reflect upon what the negative responses suggest about normative expectations of participation in the online public sphere, and how this contrasts with the realities of algorithmically structured online spaces.